A prospective trial of abiraterone acetate plus prednisone in Black and White men with metastatic castrate‐resistant prostate cancer. Issue 16 (5th May 2021) - George, Daniel J.; Halabi, Susan; Heath, Elisabeth I.; Sartor, A. Oliver; Sonpavde, Guru P.; Das, Devika; Bitting, Rhonda L.; Berry, William; Healy, Patrick; Anand, Monika; Winters, Carol; Riggan, Colleen; et al.
Abstract : Background: Retrospective analyses of randomized trials suggest that Black men with metastatic castration‐resistant prostate cancer (mCRPC) have longer survival than White men. The authors conducted a prospective study of abiraterone acetate plus prednisone to explore outcomes by race. Methods: This race‐stratified, multicenter study estimated radiographic progression‐free survival (rPFS) in Black and White men with mCRPC. Secondary end points included prostate‐specific antigen (PSA) kinetics, overall survival (OS), and safety. Exploratory analysis included genome‐wide genotyping to identify single nucleotide polymorphisms associated with progression in a model incorporating genetic ancestry. One hundred patients self‐identified as White (n = 50) or Black (n = 50) were enrolled. Eligibility criteria were modified to facilitate the enrollment of individual Black patients. Results: The median rPFS for Black and White patients was 16.6 and 16.8 months, respectively; their times to PSA progression (TTP) were 16.6 and 11.5 months, respectively; and their OS was 35.9 and 35.7 months, respectively. Estimated rates of PSA decline by ≥50% in Black and White patients were 74% and 66%, respectively; and PSA declines to <0.2 ng/mL were 26% and 10%, respectively. Rates of grade 3 and 4 hypertension, hypokalemia, and hyperglycemia were higher in Black men. Conclusions: Multicenter prospective studies by race are feasible in men with mCRPC but require less restrictive eligibility. Despite higher comorbidity rates, Black patients demonstrated rPFS and OS similar to those of White patients and trended toward greater TTP and PSA declines, consistent with retrospective reports. Importantly, Black men may have higher side‐effect rates than White men. This exploratory genome‐wide analysis of TTP identified a possible candidate marker of ancestry‐dependent treatment outcomes. Abstract : This is the first prospective, race‐stratified study in advanced prostate cancer demonstrating important trends in outcomes previously only observed in retrospective reports. These results demonstrate the feasibility of this approach in a multicenter setting and establish important preliminary data with regard to differences in toxicity profiles and predictive biomarkers by race.